2012
DOI: 10.1021/ml300065z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitumor Activity of Ellagic Acid Peracetate

Abstract: Ellagic acid (1) was synthesized for the first time from methyl gallate through 3-pentagalloylglucose (α-PGG), and ellagic acid peracetate (3,4,3′,4′-tetra-O-acetylellagic acid, 2) was derived from 1 by acetylation. Oral administration of 2 suppressed melanoma growth significantly in C7BL/6 immunocompetent mice without having any effect on natural killer (NK) cell activity. Comparison of the immunoenhancing activities of 1 and 2 indicated that the latter compound increased white blood cell quantities in periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“… 47 After HT-29 cells were treated with compound 1 or etoposide at different concentrations, annexin V flow cytometry was performed following a previous protocol. 48 Treatment of HT-29 cells with 1 or 5 μM phyllanthusmin D ( 1 ) for 72 h resulted in 28.2% or 30.3% of HT-29 cells undergoing early apoptosis, respectively, while the analogous values for the vehicle control or 1 or 5 μM etoposide treatments were 3.9%, 12.9%, and 12.5%, respectively (Figure 5 ). Also, 1 induced 27.3% (at 1 μM) and 38.0% (at 5 μM) HT-29 cell apoptosis at the late stage, while the vehicle control or 1 or 5 μM etoposide treatments induced 8.6%, 19.8%, or 25.3% HT-29 cell apoptosis at this stage, respectively (Figure 5 ).…”
Section: Resultsmentioning
confidence: 96%
“… 47 After HT-29 cells were treated with compound 1 or etoposide at different concentrations, annexin V flow cytometry was performed following a previous protocol. 48 Treatment of HT-29 cells with 1 or 5 μM phyllanthusmin D ( 1 ) for 72 h resulted in 28.2% or 30.3% of HT-29 cells undergoing early apoptosis, respectively, while the analogous values for the vehicle control or 1 or 5 μM etoposide treatments were 3.9%, 12.9%, and 12.5%, respectively (Figure 5 ). Also, 1 induced 27.3% (at 1 μM) and 38.0% (at 5 μM) HT-29 cell apoptosis at the late stage, while the vehicle control or 1 or 5 μM etoposide treatments induced 8.6%, 19.8%, or 25.3% HT-29 cell apoptosis at this stage, respectively (Figure 5 ).…”
Section: Resultsmentioning
confidence: 96%
“…In vivo oral administration of EA-peracetate significantly suppressed melanoma growth in C57BL/6 mice and increased white blood cell number in peripheral blood. Both the antitumor efficacy and immune stimulation exerted by EA-peracetate in an in vivo model of melanoma were greater as compared to those induced by EA, suggesting that appropriate chemical modifications might enhance EA antitumor potential [ 89 ]. Finally, by using chitosan films as local carrier of EA, Kim and collaborators demonstrated that films containing 0.5 and 1% of the polyphenolic compound ( w / v ) exerted potent antiproliferative and apoptotic effects in human melanoma WM115 cells [ 90 ].…”
Section: In Vitro and In Vivo Activity Of Ellagic Acid In Differenmentioning
confidence: 99%
“…47 After HT-29 cells were treated with compound 1 or etoposide at different concentrations, annexin V flow cytometry was performed following a previous protocol. 48 Treatment of HT-29 cells with 1 or 5 μM phyllanthusmin D (1) for 72 h resulted in 28.2% or 30.3% of HT-29 cells undergoing early apoptosis, respectively, while the analogous values for the vehicle control or 1 or 5 μM etoposide treatments were 3.9%, 12.9%, and 12.5%, respectively ( Figure 5). Also, 1 induced 27.3% (at 1 μM) and 38.0% (at 5 μM) HT-29 cell apoptosis at the late stage, while the vehicle control or 1 or 5 μM etoposide treatments induced 8.6%, 19.8%, or 25.3% HT-29 cell apoptosis at this stage, respectively ( Figure 5).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Annexin V Staining Method. As described in previous studies, 48 HT-29 cells were treated with the vehicle control or etoposide (1 or 5 μM) or 1 (1 or 5 μM) for 72 h. The cells were washed with annexin V binding buffer, centrifuged at 300g for 10 min, and suspended (1 × 10 6 ) in 100 μL of 1× annexin V binding buffer. Then, 10 μL of annexin V-APC was added to the suspension.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%